EFEKTIVITAS EKSTRAKURIKULER ROHANI ISLAM DALAM PENANAMAN NILAI-NILAI KARAKTER RELIGIUS PESERTA DIDIK DI SMA NEGERI 1 SAMBAS - Suhada Suhada (Tarbiya Islamica, 2015)
The purpose of this study is to reveal about 1) the cultivation of the values ​​of the religious character of students; 2) the method of inculcating the religious character values ​​of students; 3) obstacles in inculcating the values ​​of the religious character of students; 4) the results of inculcating the values ​​of the religious character of students. This study uses a qualitative approach with a descriptive type of research. Data collection techniques using interviews, observation, and documentation. The data analysis techniques used are data collection, data reduction, data presentation and drawing conclusions and verification. The results in this study are the implementation of spiritual extracurriculars in inculcating the values ​​of the religious character of students starting with reading prayers before studying and closing the learning with prayers again. activities are carried out by informing the routine schedule, preparing materials and compiling work programs, Islamic spiritual extracurricular methods in instilling the values ​​of the religious character of students, namely through a) advice method b) habituation method c) exemplary method, Islamic spiritual extracurricular barriers in inculcating values The values ​​of the religious character of students include those of the students themselves, inadequate facilities and infrastructure, it is difficult to get along with new friends, the results of inculcating the values ​​of the religious character of students after participating in spiritual activities, students gain knowledge that is very beneficial for changes in their lives. students, especially in the religious field, which has a religious character. For example, praying in congregation in the mosque, reading and writing the Qur'an, fasting in the month of Ramadan and paying more attention to the etiquette of eating, drinking and sleeping.